Learning e-commerce web design engineering: Towards discovery of service innovational opportunities - Lee, Chien Sing *; Wong, Daniel K. (2016)
Graduates are expected to be skilled across disciplines and provide holistic solutions. Hence, scaffolding is crucial as transfer of learning does not occur naturally and teaching learning strategies found to be effective for experts may not be adopted similarly for novice learners. We hypothesize that if we can help students to model in relation to the ecosystem, they should be able to identify or discover opportunities, strategically assess technologies and create new innovations and interactions for e-commerce Websites. For goal-based scaffolding, we use technology-assisted design thinking, embedded formative assessments. We study more effective ways to develop: a) skills useful to the design and development of sustainable Web systems and services and possibly sustainable smart services in the future by relating business to technology and impacts on society; b) epistemic agency for lifelong learning.